DEVELOPING SOCIAL-EMOTIONAL COMPETENCE TO ENHANCE TEACHER PERFORMANCE IN SCHOOLS: A BIBLIOMETRIC REVIEW - Abu Zarim, Nor Zairos; Surat, Shahlan (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
This bibliometric review investigates the evolving landscape of research on developing Social-Emotional Competence (SEC) to enhance teacher performance in schools. SEC is increasingly recognized as a foundational element in fostering teacher well-being, classroom management, and student academic success. However, the literature on this topic remains dispersed, lacking a cohesive synthesis of research trends, collaborations, and thematic developments. The study aims to address this gap by systematically analyzing scholarly output using data extracted from the Scopus database. A total of 881 peer-reviewed articles published between 2015 and May 2025 were selected based on refined inclusion criteria. Data cleaning was performed using OpenRefine, while Scopus Analyzer provided insights into annual publication trends, top contributing countries, and citation metrics. VOSviewer was employed to map co-authorship networks, keyword co-occurrences, and collaborative link strengths. The analysis reveals a substantial rise in publication volume after 2020, peaking in 2024, indicating growing global interest in integrating SEC into teacher training and practice. The United States leads in publication count and collaboration strength, followed by China, the United Kingdom, and Australia, reflecting diverse international engagement. Highly cited works highlight the interdisciplinary nature of the field, merging educational psychology, emotional intelligence, and digital learning contexts. Dominant keywords such as “emotions,” “emotional competence,” and “teacher well-being” suggest a research focus on emotional regulation, professional development, and student-teacher relationships. Despite active research growth, limited cross-country collaboration presents opportunities for broader international integration. This review contributes a structured overview of the knowledge base, identifies emerging themes and research gaps, and offers direction for future studies and educational policies aimed at improving teacher performance through social-emotional development.